2020
DOI: 10.1055/s-0040-1718750
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease and Need for Antireflux Surgery in Children with Cystic Fibrosis: A Systematic Review on Incidence, Surgical Complications, and Postoperative Outcomes

Abstract: Introduction Gastroesophageal reflux disease (GERD) is associated with accelerated decline in lung health in children with cystic fibrosis (CF). Thus, antireflux surgery (ARS) is offered to a selected CF cohort with refractory GERD, but outcomes remain poorly investigated. This study aimed to determine the incidence of GERD in children with CF and to evaluate complications and outcomes of ARS. Materials and Methods A systematic literature-based search was conducted using various online databases acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…CF patients are at increased risk of exposure to the different antibiotics in CF patients that could alter the microbiome in the GI tract of those patients, making them more prone to different mucosal diseases including EoE [ 12 13 14 ]. CF patients also tend to have more GERD than the general population [ 29 30 31 ]. This could result in an increase in the use of PPIs which can be associated with an increase in EoE as reported previously [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…CF patients are at increased risk of exposure to the different antibiotics in CF patients that could alter the microbiome in the GI tract of those patients, making them more prone to different mucosal diseases including EoE [ 12 13 14 ]. CF patients also tend to have more GERD than the general population [ 29 30 31 ]. This could result in an increase in the use of PPIs which can be associated with an increase in EoE as reported previously [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review on incidence, surgical complications, and postoperative outcomes evaluated the results of antireflux surgery, including the Nissen fundoplication, for infants and children with CF 21 . This study showed that antireflux surgery improved GERD symptoms with a potential reduction in lung function decline.…”
Section: Pathophysiology Of the Cf Gi Tractmentioning
confidence: 96%
“…Basic nutritional care includes a high-calorie, high-fat diet associated with PERT, and fat-soluble vitamins supplementation. Morbidities like pulmonary infections, gastrointestinal complication (gastro-esophageal reflux, constipation, distal intestinal obstructive syndrome) can decrease appetite and determine inadequate nutrient intake [ 31 , 32 , 33 ].…”
Section: Clinical Considerations Of Exocrine Pancreatic Insufficiencymentioning
confidence: 99%